EXPRESSING ELDERLY AGE THROUGH IDIOMATIC EXPRESSIONS IN THE ENGLISH AND RUSSIAN LANGUAGES - Khamrakulova Sabina Feyruzkhanovna (Western European Studies, 2024)
Any language is considered to be the means to reflect cultural and national mentality of its speakers as well as to reproduce the images of national pictures of the world incarnating them through alphabetical units. Currently, the research of the peculiarities of phraseology through the phraseological units characterized with heightened sociality and interaction with the society is one of the most perspective tendencies in modern linguistics. Phraseological units expressing a human age can be referred to such units as being one of the language features existing among any nation and at all times they can impart a lot of interesting facts about the past and present of any nation. This article reveals distinctive features of phraseological units expressing elderly age in English and Russian from comparative aspect so that it will be possible to identify universal and unique language phenomena between the two languages
Keywords: language; cultural mentality; national mentality; human age